Prevalence of vertically transmitted Neospora caninum amongst beef cattle in Phayao, Thailand. (June 2019) - Japa, Ornampai; Nuangmek, Aniroot; Prakhammin, Khanuengnij; Flynn, Robin J.
Abstract: Neospora caninum, the causative agent of neosporosis, is recognised as a significant trigger of abortion and productivity losses in cattle worldwide. Current information regarding to the prevalence of N. caninum in Thailand is limited due to the limitations of detection methods and the difficulty of recovering of viable parasite. Vertical transmission is the main route of N. caninum infection in cattle. Therefore, detection of N. caninum DNA in placental tissue could be a possible means of laboratory diagnosis of neosporosis in live animals, particularly in the context of transplacental transmission. The aim of this study was to investigate the prevalence of transplacentally transmitted N. caninum infection in female beef cattle in the northern Thai province of Phayao by detection of N. caninum DNA in bovine placenta by PCR. A total of 96 bovine placentas were collected from 7 districts of Phayao. Our result indicated that overall PCR prevalence of N. caninum in cattle in this area was 36.5% varying from 16.7–50.0% between districts. The districts with the highest prevalence of infection were Muang (50.0%) and Mae Chai (44.7%). The proportion of N. caninum infection was quite high suggesting that newborn calves were at risk of congenital infection. This study provides a current snapshot of the status of bovine neosporosis in Phayao which could lead to the development of effective strategies for prevention and control this disease.